Quality of Care Indicators for Head and Neck Cancers: The Experience of the European Project RARECAREnet - Trama, Annalisa; Botta, Laura; Foschi, Roberto; Visser, Otto; Borras, Josep Maria; Žagar, Tina; Primic-Žakelj, Maja; Bella, Francesca; Dimitrova, Nadya; Gatta, Gemma; Licitra, Lisa (Frontiers in Oncology, 2019)
Background Monitoring and improving quality of cancer care has become pivotal today. This is especially relevant for head and neck cancers since the disease is complex, it needs multi therapy, patients tend to be older, they tend to have comorbidities and limited social support. However, information on quality of care for head and neck cancers is scarce. In the context of the project “Information Network on Rare Cancers” we aimed to identify indicators of quality of care specific for the head and neck cancers management and to measure the quality of care for head and neck cancers in different EU Member States. Methods We defined indicators of quality of care for head and neck cancers based on a multidisciplinary and expert-based consensus process at a European level. To test the proposed indicators, we performed an observational population-based retrospective study in four countries (Ireland, Italy, Netherlands and Slovenia) in the years 2009-2011. Results The main quality indicators identified are: availability of formalised multidisciplinary team, participation in clinical and translational research; timeliness of care, high quality of surgery and radiotherapy and of pathological reporting. For head and neck cancers, the quality of care did not reach the optimal standards in most of the countries analysed. A high proportion of patients was diagnosed at an advanced disease stage, showed delays in starting treatment (especially for radiotherapy), and there was only a very limited use of multi therapy. Conclusions According to the achieved consensus, indicators of quality of care for head and neck cancers have to cover the patient journey (i.e., diagnosis and treatment). Our results, showed suboptimal quality of care across countries and call for solutions for ensuring good quality of care for head and neck cancer patients in all EU countries. One possible option might be to refer head and neck cancer patients to specialised centres or to networks including specialised centres.